Austrodiplostomum compactum (Lutz, 1928) (Digenea, Diplostomidae) infecting Geophagus proximus Castelnau, 1855 (Cichlidae, Perciformes) in the Tietê River, Nova Avanhandava Reservoir, municipality of Buritama, São Paulo State, Brazil - Zica, Erica de Oliveira Penha [UNESP]; Wunderlich, Alison Carlos [UNESP]; Ramos, Igor Paiva [UNESP]; Silva, Reinaldo José da [UNESP] (My University, 2010)
This study aimed to evaluate the infection by the Austrodiplostomum compactum (Lutz, 1928) metacercariae in the eyes of Geophagus proximus Castelnau, 1855 from the Nova Avanhandava Reservoir, medium Tietê river, municipality of Buritama, São Paulo State, Brazil. The parasites were collected from vitreous humor, fixed in AFA solution under cover slip pressure, stained with carmine and cleared with creosote. The morphometric analysis was performed using a computerized system for analysis of images QWin Lite 2.5 (Leica). Fourtyone G. proximusspecimens were collected and 38 were infected in the humor vitreous with A. compactum metacercariae (prevalence = 97%). Four hundred eighty six metacercariae were recovered, range from 1 to 194 in the studied specimens. The mean intensity of infection and abundance were 12.8 ± 5.1 and 11.8 ± 4.75, respectively.

Este estudio tuvo como objetivo evaluar la infección por metacercanias de Austrodiplostomum compactum (Lutz, 1928) en los ojos de Geophoagus proximus Castelnau, 1855 del río Tietê Nova Avanhandava medio Presa, Municipio de Buritama, Estado de São Paulo, Brasil. Los parásitos fueron recogidos de humor vítreo, fijados en solución AFA y teñidos con carmín y aclarados con creosota. El análisis morfométrico se realizó con un sistema informatizado de análisis de imágenes QWin Lite 2,5 (Leica). Cuarenta y un ejemplares de G. proximus fueron colectados y 38 fueron infectados en el humor vítreo con metacercarias A. compactum (prevalencia = 97%). Cuatrocientos ochenta y seis metacercarias fueron recuperadas, rango 1 a 194 en los especímenes estudiados. La intensidad media de la infección y la abundancia fueron 12,8 ± 5,1 y 11,8 ± 4,75, respectivamente.
Austrodiplostomum compactum (Lutz, 1928) (Digenea, Diplostomidae) infectando Geophagus proximus Castelnau, 1855 (Cichlidae, Perciformes) en el río Tietê, reservorio Nova Avanhandava, municipalidad de Buritama, estado de São Paulo, Brazil
Keywords: Diplostomidae; Fish; Helminths; Tietê River; Diplostomidae; Helmintos; Peces; Río Tietê